Perbedaaan Minat Berbelanja Offline dan Online pada Peserta Didik Desain dan Produksi Busana SMK Negeri 3 Blitar - Danada Syamsa Belia; Lutfiyah Hidayati; Peppy Mayasari; Ma’rifatun Nashikhah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Technological developments have influenced various aspects of life, one of which is shopping methods. Consumers now have two main options for shopping: offline and online. Competition between offline and online stores is increasingly fierce, so it is important to understand the differences in consumer shopping interests in both methods. This study aims to identify whether there are significant differences in offline and online shopping interests and to measure the magnitude of these differences. The method used in this study is quantitative with a difference test approach. The study was conducted at SMK Negeri 3 Blitar with students from the Fashion Design and Production department as research subjects. The data collection technique was carried out using a questionnaire distributed to respondents. The collected data were then analyzed using a paired two-sample T-test to determine differences in shopping interests between offline and online. After that, the effect size calculation was carried out using Cohen's D to measure the magnitude of the existing differences. The results showed that there are significant differences in interest in offline and online shopping. The results of the T-test indicate a clear difference between these two shopping methods. Furthermore, the Cohen's D effect size analysis produced a value of -0.940, which indicates that the difference is in the large category. This means that Fashion Design and Production students at SMK Negeri 3 Blitar are more likely to have a higher interest in online shopping than offline shopping. This is due to the convenience and practicality of online shopping, where consumers do not need to come to a physical store to make a transaction. This study provides an overview of how shopping interest can be influenced by the ease of access offered by online shopping.